Global challenges in human immunodeficiency virus and syphilis coinfection among men who have sex with men. Issue 11 (1st November 2016) - Roberts, Chelsea P.; Klausner, Jeffrey D.
ABSTRACT: Introduction : Syphilis and human immunodeficiency virus (HIV) coinfection disproportionately affects men who have sex with men (MSM), and the rate of coinfection has been increasing over the last decade. HIV and syphilis coinfection is particularly challenging because the infections interact synergistically thereby increasing the risk of acquisition and transmission as well as accelerating disease progression. Areas covered : This paper reviews and summarizes the epidemiology, pathogenesis, diagnosis, clinical management and prevention of HIV and syphilis coinfection among MSM. Expert commentary : Research does not support a different syphilis treatment for coinfected individuals; however, coinfection may warrant a recommendation for antiretroviral therapy. In order to reverse the epidemic of syphilis and HIV coinfection, there needs to be greater awareness, improved cultural sensitivity among health care providers, improved access to preventative services and increased screening for syphilis and HIV.